Rhagoletis cerasi Loew (Diptera: Tephritidae) – Biological Characteristics, Harmfulness and Control - Perić, Pantelija (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The European cherry fruit fly, Rhagoletis cerasi Loew (Diptera: Tephritidae), is a highly destructive pest in sweet and sour cherry orchards with a distribution area throughout Europe and the temperate regions of Asia. It occurs regularly in all production regions of these fruit species in Serbia, damaging up to 10% of cherries in commercial production, while damage can go up to 100% in orchards and on solitary threes unprotected by control measures. In Serbia, European cherry fruit fly most often attacks and damages fruits of the late-ripening cultivars of sweet cherry (Van, Stela, Hedelfinger, Bing, Lambert, Drogan’s Yellow). After a sweet cherry harvest, adults migrate to sour cherry where they continue feeding and ovipositing in half-mature sour cherries (prevailingly the domestic ecotype Oblačinska). During their activity period, larvae damage the fruits, so that they can no longer be consumed either fresh or processed. The high percentage of sour cherries damaged by R. cerasi has become a factor limiting exports because the intensity of infestation of this fruit exceeds permissible limits. Pesticide use for controlling this pest, especially in integrated production, is based on a very poor selection of insecticides which cause problems with residual ecotoxicity. Consequently, alternative measures for controlling European cherry fruit fly have been intensively studied over the past few years. This work surveys up-to-date results of various studies on the European cherry fruit fly as a very important pest in Serbia and other South and Mid-European countries. The work contains detailed descriptions of its biological characteristics, flight phenology, infestation intensity and possibilities of fly control in sweet and sour cherry production areas.